School inspection in the educational work of Martín Rodríguez Vivanco - Lídice Mesa Gómez (ADIDE Federación, 2015)
Martin Rodríguez Vivanco was a valuable exponent of the Cuban education during the republican period. As follower of the pedagogic thought of the Cuban XIX century, he tried to sit down the bases of the pedagogy with the introduction of the subjects pedagogic Sociology and Technique of the school inspection in the School of Pedagogy of the University of Havana. The present work is a result of the doctorate thesis of its author's and he intends to reveal the conceptions on the school inspection in this educational work. Their conceptions on this area were very revolutionary for their time. The functions of the inspection, their agents, the historical reconstruction of the school inspection in Cuba, among other elements is good at the present time to clarify and to sustain the roots of the Cuban pedagogy.